Factors causing regional differences in China's residential CO2 emissions—evidence from provincial data. (1st July 2019) - Miao, Lu; Gu, Huijie; Zhang, Xiwei; Zhen, Wei; Wang, Mingyue
Abstract: Residential energy consumption has increased sharply in China and is further expected to grow owing to rapid economic growth and improved living standards. The residential sector will be one of the leading drivers of greenhouse gas emissions. Therefore, this study divides China into three areas considering regional differences and re-investigates the influence of human activities on residential CO2 emissions in China's 28 provinces during 2000–2016. Using an extended stochastic impacts by regression on population, affluence, and technology model, the key factors behind residential CO2 emissions are investigated. The main findings are as follows: Residential CO2 emissions in China have regional characteristics and the effects of urbanization, energy intensity, and price elasticities vary among the three regions. GDP per capita is the key factor and positively influences total residential CO2 emissions. By adding the squared and cubed terms of GDP per capita, the environmental Kuznets curve hypothesis is tested for all regions and for China overall. The results confirm the environmental Kuznets curve in the eastern region and show an "N" shaped curve at the national level.